Implikasi Peran Financial Technology Dalam Meningkatkan Efektivitas Sistem Informasi Akuntansi - Hanifah, Risti Ulfi; Rizkiana, Citra; Agusrina, Yohana; Sulistyawati, Ardiani Ika; Santoso, Aprih (Politeknik Ganesha Medan, 2024)
In the era of internet technology, it has a lot of impact on all lines of the company's sector and daily life, one of which is the existence of supporting applications that can be used with the aim of helping in carrying out daily activities. In addition, the development of digital technology is very influential in the order of life both in the social and economic fields, which initially in paying had to meet face to face and carry a certain amount of cash, now can make remote transactions in seconds. This era is called the era of digital economy or fintech which enters the age of time efficiency. The age and productivity of a human being have limits, a person can be said to be unable to be productive again at a certain period of time. If someone is said to be no longer productive, then that person can be said to be someone who has reached the retirement age limit. Of course, in this case, it requires adequate infrastructure support. Currently, the government has an Old Age Savings program and a pension program for someone who has entered the retirement age limit. PT Taspen is one of the companies that organizes and manages pension funds, especially for the State Civil Apparatus (ASN). In the era of internet technology, it has a lot of impact on all lines of the company's sector and daily life, one of which is the existence of supporting applications that can be used with the aim of helping in carrying out daily activities. In addition, the development of digital technology is very influential in the order of life both in the social and economic fields, which initially in paying had to meet face to face and carry a certain amount of cash, now can make remote transactions in seconds. This era is called the era of digital economy or fintech which enters the age of time efficiency. The age and productivity of a human being have limits, a person can be said to be unable to be productive again at a certain period of time. If someone is said to be no longer productive, then that person can be said to be someone who has reached the retirement age limit. Of course, in this case, it requires adequate infrastructure support. Currently, the government has an Old Age Savings program and a pension program for someone who has entered the retirement age limit. PT Taspen is one of the companies that organizes and manages pension funds, especially for the State Civil Apparatus (ASN). This research took the object at PT Taspen (Persero) KCU Semarang. The purpose of this study is to find out how fintech is used in organizing and managing pension funds. This research is qualitative research, with research methods using interview techniques. There were 3 participants, consisting of financial head sector, customer service and human resource department. In testing data credibility, researchers use riangulation of data sources and trigulation of data collection techniques. The results of this study show that PT Taspen already has fintech application facilities that are used for retirees easily and can be applied properly, and there are facilities for visiting participants' homes for participants who are sick and cannot take pension funds. On the other hand, financial management using fintech has been implemented well and efficiently, so that financial transparency and accountability are well controlled and monitored. However, based on interviews in customer service, there are obstacles in the file that are not appropriate and there is a passive account attachment